Oil palm residue biodelignification by bacillus cereus ligninase from coptotermus curvignathus gut for handsheet production - Mutia Syarifah, Sharfina (2020)
Conventional methods used to delignify lignin using mechanical and chemical process consumed high energy and environmentally unfriendly. Meanwhile, the demand for paper substantially increased with declined wood fibres. In this study, Bacillus cereus isolated from termite species Coptotermes curvignathus gut’s bacteria was tested for biodelignification capability on palm oil biomasses: oil palm leaves (OPL), oil palm trunk (OPT) and empty fruit bunch (EFB). The biopulp was produced under submerged fermentation (SmF) using Luria Bertani (LB) broth at pH 6.5, 120 rpm and 37 °C for 7 days. The enzyme expression was partially characterized and protein sequenced. There were 11 enzymes responsible for lignin degradation such as 4aminobutyrate